DIY Tomography sample holder. (September 2015) - Lari, L; Wright, I; Boyes, E D
Abstract: A very simple tomography sample holder at minimal cost was developed in-house. The holder is based on a JEOL single tilt fast exchange sample holder where its exchangeable tip was modified to allow high angle degree tilt. The shape of the tip was designed to retain mechanical stability while minimising the lateral size of the tip. The sample can be mounted on as for a standard 3mm Cu grids as well as semi-circular grids from FIB sample preparation. Applications of the holder on different sample systems are shown.